Etnografisk fiktion: Om kvinnors liv i det nya Irland - Wulff, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
Ireland’s strong literary tradition was created by writers from James Joyce to Seamus Heaney, and literature was a prominent part of the national cultural revival in the late 19th century. It was the poet Yeats who initiated what has been called the literary movement which had a political impact on Ireland’s passage into independence. Irish literary theorist Declan Kiberd argues in his Inventing Ireland that it was with this literary movement that Ireland became a modern nation. Now the literary tradition is continued by an acclaimed generation of fiction writers. They tend to reflect on the sudden social change which the so called Celtic Tiger, the economic boom in the late 20th century brought to the Republic of Ireland. In my anthropological study of Irish literature, it was novels and short stories by Éilís Ní Dhuibhne (pronounced "Eilish Nee Gwivna" in English) that first pointed me to the concept of ethnographic fiction. The aim of this article is to explore how Ní Dhuibhne’s writings on women and girls can be used as ethnography. This also evokes questions about the relationship between ethnography as a method and text on one hand and ethnography and fiction on the other. Ní Dhuibhne collects material for her fiction from the type of ethnographic observation and note taking which originates in anthropology and ethnology. With a doctorate in Irish folklore, she has an eye for ethnographic details especially the predicaments of women in Ireland who are trying to combine traditional family life with modern careers. This leads over to issues on Irish writers and their fiction in the world.